Hydrological assessment of field-scale GeoWaste and waste rock test piles - Hassanzadeh Gorakhki, Mohammad Reza, author; Bareither, Christopher, advisor; Shackelford, Charles, committee member; Scalia, Joseph, committee member; Heyliger, Paul, committee member; Butters, Greg, committee member (Colorado State University. Libraries, 2020)
Mine waste rock and mine tailings are generated in substantial quantities an d must be managed to protect human health and the environment. Challenges in mine waste management facilities include geotechnical stability, environmental contamination, water management, and post operation (long term) closure. Waste rock and tailings co-disposal is a management technique that can address many of the aforementioned challenges. GeoWaste is a mixture of fast-filtered tailings and waste rock blended to isolate waste rock particles within a tailings-dominated matrix. A field-scale experiment that included a waste rock pile and GeoWaste pile was conducted at a mine in Central America to evaluate if GeoWaste suppresses sulfide oxidation and production of metal-rich acid rock drainage relative to waste rock. The objectives of this study were to (i) evaluate hydrologic performance of the piles, (ii) conduct in situ infiltration tests on the piles, (iii) determine field-scale hydraulic parameters for GeoWaste and waste rock, and (iv) develop numerical models to predict water content and oxygen concentrations within the piles. Water content, temperature, electrical conductivity, and oxygen concentration within the piles were monitored for 26 months. Sealed double ring infiltrometer tests were conducted at the end of the pile experiment and test pile subsequently were excavated to assess the spatial distribution in geotechnical characteristics. Inverse modeling was completed in HYDRUS-2D based on infiltration data to determine hydraulic conductivity and moisture retention parameters for the test piles. Field- and laboratory-scale hydraulic parameters were used in HYDRUS-1D and HYDRUS-2D to develop seepage models to predict moisture movement during the 26-month pile experiment. Oxygen concentration was predicted for the GeoWaste pile in HYDRUS-1D via the solute transport module, Fick's 2nd law, the oxygen consumption rate, oxygen diffusion in gas and water phases, and Henry's constant.